Sustainable development in Cameroon’s forestry sector: Progress, challenges, and strategies for improvement - Dieudonne Alemagi (African Journal of Environmental Economics and Management, 2020)
This paper examines initiatives formulated by the government of Cameroon to promote sustainable development within its forestry sector, and proffers a series of policy recommendations for advancing sustainable forest management in Cameroon. Since the enactment of Cameroon’s comprehensive forestry law (Law N0. 94/01 of 20th January 1994), which regulated the forestry sector in the country, the government, in particular, the Ministry of Forests and Fauna, has made a series of efforts with relevant ministries, as well as civil society to promote sustainable forest practices within its forestry sector. However, careful evaluation reveals that while these efforts have led to some progress, the sector is still plagued with a series of socio-economic and ecological challenges namely, poverty, corruption, inadequate capital and technical expertise for producing value-added wood products, illegal logging, insufficient university input, inter institutional conflicts, and inadequate monitoring. The paper concludes by advancing a series of recommendations that could be used to promote sustainable forest management in Cameroon.